Brain processing of the temporal dimension of acute pain in short-term memory. Issue 10 (October 2017) - Khoshnejad, Mina; Roy, Mathieu; Martinu, Kristina; Chen, Jen-I; Cohen-Adad, Julien; Grondin, Simon; Rainville, Pierre
Abstract : Abstract: The dynamics of noxious sensation shapes pain perception, yet the memory of the temporal dimension of pain remains almost completely unexplored. Here, brain activity during the memory of pain duration was contrasted with that associated with the memory of pain intensity using functional magnetic resonance imaging and a delayed reproduction task. Participants encoded, maintained during a short delay, and reproduced (1) the "duration" of pain (ie, onset-to-offset), (2) the "dynamics" of pain (ie, evolution of pain over time), or (3) the intensity of pain (ie, control with no explicit temporal processing required). Results show that the inferior frontal gyrus/insula and adjacent striatal structures as well as the supramarginal and middle temporal gyri are activated in the duration task compared to the control intensity task. Specific examination of the memory delay of the duration task further revealed activation in the supramarginal gyrus extending to the parietal operculum (possibly SII) and primary somatosensory cortex (SI). In contrast, the memory delay of the dynamic task involved the bilateral supplementary motor area and the frontoparietal attentional network. Although SI, SII, and insula may contribute to the memory trace of pain sensation, other areas less commonly reported in pain studies are associated with time processing and may therefore contribute to the processing of temporal aspects of pain. Results further suggest a differential role of core timing regions of the brain depending on specific task instructions and attentional allocations to the single dimension of time, as compared to the joint processing of both time and intensity. Abstract : Supplemental Digital Content is Available in the Text.This study investigates the temporal dimension of pain and shows distinctive regional brain activation associated with the short-term memory of pain dynamics and pain duration.